Language and Power in the Work of George Orwell - Škaroupka, Petr (Univerzita Pardubice, 2018)
This bachelor thesis focuses on Orwell's views and opinions on language and its connections with power, thought, reality, truth etc. With the aid of modern linguistics and philosophy, these connections and other concepts regarding language are described in the first part of the paper. On the basis of this theoretical framework, the second part of the paper analyses Orwell's views on language and power, thought, reality, truth etc. and the way Orwell implements them into his last novel Nineteen Eight-Four, particularly in the form of its artificial language Newspeak.
Jazyk a moc v díle George Orwella
Keywords: Orwell, George; jazyk; diskurz; realita; pravda; myšlení; znaky; moc; Newspeak; 1984; Devatenáct set osmdesát čtyři; lingvistika; Orwell, George; language; discourse; reality; truth; thought; signs; power; Newspeak; 1984; Nineteen Eighty-Four; linguistics